Um estudo da terminologia de certidões de nascimento: elaboração de glossário português-francês para tradutores juramentados - Catharino, Tatiane Ramazzini [UNESP] (2015)
The research currently under consideration is part of a bigger project, the LexTraJu - The lexicon of sworn translation - and intends to carry out a study of the terminology found in birth certificates of the language pair Portuguese-French, focusing on the linguistic and sociolinguistic aspects of the terms observed. For this purpose, we have created a bilingual glossary (Portuguese-French) of the terms used in birth certificates intended for the use of sworn translators. Based on a birth certificate terminology set in Portuguese, which was obtained from a previous study for a Research Internship, we are now determining the equivalences of such terms in French. The data collection and the study of the terminology in Portuguese-French were conducted based on two birth certificates corpora from Brazil and France. As the theoretical-methodological approach, we adopted the Communicative Theory of Terminology (TCT), developed, among others, by Maria Teresa Cabré (1999), Barros (2004), Dubuc (1992), Felber (1987), Krieger and Finatto (2004). The analyses we conducted regarding the terms of our glossary deal with terminological equivalence, focusing on the sociocultural similarities and differences that underlie the terms in Portuguese and their equivalents that were found in birth certificates in French. We hope to contribute with the work of translators and with the development of studies on Bilingual Terminology